Dialektika kewahyon dan keprabon dalam puisi esai Ki Ageng Selo: Sang Penakluk Petir - Supriyanto, Teguh; Widagdo, Sungging; Prasetyo, Dandung Adityo Argo; Harijanti, Sutji; Habiba, S. Alifiya (Diglosia: Jurnal Kajian Bahasa, Sastra, dan Pengajarannya, 2025)
The essay poem Ki Ageng Selo: Sang Penakluk Petir by Sri Penny has been used as teaching material for poetry writing for students at MAN 1 Grobogan. However, the structure of the essay poem is suspected to show a distance from cultural aspects. The issue that arises is whether the structural phenomena in the essay poem are appropriate to be used as teaching material. This research was conducted through a literary sociology approach using a heuristic-level semiotic method for data validation and a hermeneutic-level reading for the analysis of literary, social, and cultural rules. The research data consisted of excerpts from the lines of the poem suspected of containing ideology, as per the research problem. The research results are based on the use of Bourdieu's cultural arena theory, revealing a dialectic between 'kewahyon' and 'keprabon' as well as the matrix as the center of meaning. In the cultural aspect, the matrix can be understood through actual and potential hypogrammatics. The figure Ki Ageng Selo experiences a tension (dialectic) between ambition and expectation. The study concludes that the essay poem Ki Ageng Selo: The Conqueror of Lightning can be recommended as learning material for the younger generation of the nation.